Prediksi Stok Otomatis dengan AI untuk Mengoptimalkan Pengeluaran Retail Sebagai Inovasi dalam Bisnis - Rachmah, Nur Nabillah; Fadil, Cholid (Peneliti.net, 2024)
This research paper explores the transformative potential of integrating Artificial Intelligence (AI) and Blockchain technologies in business innovation (BI-AIBT), with a focus on the retail sector. By investigating the impact of BI-AIBT on operational challenges, this research highlights how AI-driven automated stock prediction, exemplified by the Smart Inventory AI (SI-RAI) solution, can address critical issues in inventory management, supply chain inefficiencies, and interdepartmental collaboration. Through qualitative research involving a literature study, this paper reveals the urgent need for an efficient solution to optimize spending, improve customer satisfaction, and enable data-driven decision-making. The findings underscore the great expectations for SI-RAI, signifying its potential to revolutionize retail operations by offering predictive insights, fostering interdepartmental collaboration, and ultimately driving efficiency, financial growth, and market competitiveness.